Analysis Of Service Quality and Punctuality of Cargo Delivery on Customer Satisfaction at PT Samudera Indonesia - Agus Setiawan; Siti Nurhayati; Jennifer Vanessa Rose; Destyan Nur Ramadhan (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The purpose of this study is to analyze the relationship between the quality of sea freight services with the punctuality of cargo delivery with the level of customer satisfaction at PT Samudera Indonesia. This study used survey methods with questionnaires and quantitative data collection tools. The results showed that the quality of sea transportation services had a significant effect on customer satisfaction. Customers who feel they are receiving quality service tend to be more satisfied. In addition, the punctuality of cargo delivery also has a major effect on customer satisfaction. These results provide important insights for PT Samudera Indonesia to improve service quality and delivery timeliness to meet customer expectations and maintain their satisfaction in the fierce sea transportation industry competition.